ANALISIS KRITIK TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 36/PUU-X/2012 - Simon Butt; Fritz Edward Siregar (Fakultas Hukum Universitas Gadjah Mada, 2013)
This article discusses the Constitutional Court Judgment No. 36/PUU-X/2012. In this judgment, the majority of the Justices decided that the 1945 Constitution requires the State to exercise direct control over the upstream oil and gas activities. We will criticise the Justices’ deliberation that underlies the decision. The Court failed to shed light on questions pertaining to the legal rationale for ‘five activities’ doctrine that form the framework of ‘State control’ per Article 33 (3) of the Constitution and to the procedures in determining the priority ranking. In addition, the majority Justices are deemed to have left the question of whether the State is able to manage oil and gas industry unanswered. We will also describe how this judgment might result in the declining interest of foreign investors to invest in Indonesia, particularly inthe field of exploration and exploitation of natural resources. Artikel ini membahas Putusan Mahkamah Konstitusi Nomor 36/PUU-X/2012. Dalam putusan tersebut, mayoritas Hakim Konstitusi memutus bahwa UUD NRI Tahun 1945 mensyaratkan Negara secara langsungmenguasai kegiatan hulu Migas. Diuraikan kritik terhadap pertimbangan hukum dari putusan, yakni kelalaian Mahkamah tidak menjelaskan dari mana asal ‘lima kegiatan’ sebagai komponen ‘penguasaan negara’ dalam Pasal 33(3) UUD NRI Tahun 1945, bagaimana menentukan prioritas rangkingnya, dan perihal mayoritas Hakim Konstitusi yang tidak menentukan apakah Negara mampu mengelola industri Migas. Selain itu, diuraikan pula bahwa putusan tersebut berpotensi mengurangi ketertarikan investor asing untuk menanam modalnya di Indonesia, khususnya di bidang eksplorasi dan eksploitasi sumberdaya alam.